Internal control, reporting failures and lack of scientific methodology for reporting – Status of the Al- Bireh- Palestine municipality – - Al- Tawil, Ziyad Said (Journal of Economic, Administrative and Legal Sciences, 2021)
The question that the research seeks to answer is the relationship of good supervisory administrative reports to achieving the goals of the organization, and helping managers to show the spirit of work interest in making their administrative decisions and taking those decisions away from their personal aims and interests. The scientific and applied importance of research appears in an attempt to shed light on the importance of internal control and its correct scientific and technical reports in developing and maximizing the benefit of the organization. The researcher applies his hypotheses to the municipality of Al- Bireh- Palestine as an applied case and studies the monitoring reports from the beginning of 2013 until the beginning of 2020 and the violations that were shown or not shown by the supervisory reports in some of the decisions taken at the time and whether the weakness of these reports had a role in the growth and increase of violations and deviation from the regulations and the policies in place at the time or not.The research assumes in general that the more supervisory reports are prepared in a wrong way technically and administratively, with the knowledge or ignorance of the source of those reports, the more deviation the administration and its decisions are from the course, objectives, laws and policies set for this organization.
Keywords: internal control; audit reports; Al-Bireh municipality; scientific methodology for audit reports